2020
DOI: 10.1111/jgh.14958
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor in upper gastrointestinal fecal microbiota transplant: A systematic review and analysis

Abstract: Background and Aims Fecal microbiota transplantation (FMT) is used in recurrent Clostridioides difficile infections. However, protocols are facility dependent, and one variable is whether pre‐procedural proton pump inhibitors (PPIs) are given. In theory, PPIs reduce acidity and protect the transplanted microbiome for the most potent dose. We conducted a systematic review to study the effect of PPIs on FMT delivered by upper gastrointestinal (GI) routes. Methods We searched Pubmed/Medline, Cochrane Library, Emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…15). That study was also the first to describe the prevalence of granulomas in CD in a non‐Western population, which was 50%, which was within the range in Caucasians of 13–67% …”
mentioning
confidence: 62%
See 1 more Smart Citation
“…15). That study was also the first to describe the prevalence of granulomas in CD in a non‐Western population, which was 50%, which was within the range in Caucasians of 13–67% …”
mentioning
confidence: 62%
“…In this issue of JGH , Hong et al . evaluated the significance of epithelioid granulomas in CD based on a meta‐analysis of prior publications.…”
mentioning
confidence: 99%
“…Furthermore, a meta-analysis from Hong et al. [ 74 ] proved there was no statistically significant benefit from the routine use of pre-treatment with PPIs in the FMT protocol compared to no PPI-used protocols.…”
Section: Discussionmentioning
confidence: 99%
“…PPIs might change microbiota [118] with moderate alterations occurring to both upper and distal gut microbiota [119]. No clinically significant benefit from routine use of PPIs in FMT protocols were identified [120,121]. Considering all these aspects, the WG suggested that PPI use should be avoided peri-procedurally, considering conflicting results on PPIs' effect in this setting, until further steps are taken to optimize protocols for safety and efficacy.…”
Section: Ppi Usementioning
confidence: 99%